Cooperation networks between authors and institutions in Social Sciences within the Colombian scientific model: comparison by gender and area of knowledge - Hernando Ávila-Toscano, José; Marenco-Escuderos, Ailed Daniela; Romero-Pérez, Ivón Katherine (Revista General de Información y Documentación, 2019)
This study analyzed the structural properties in networks of co-authorship and institutional collaboration in Social Sciences, based on articles published between 2006 and 2015 by 3,804 authors from seven disciplines. The structural characteristics were calculatedthrough Social Network Analysis and were compared according to the gender of the authors and areas of knowledge. No significant differences were found in relation to gender, but disciplinary differences were observed in the closeness and relative importance of the authors. The institutional networks showed low density, high fragmentation and little cohesion. In the social sciences in Colombia the number of women with productivity similar to men grows; institutionally, strategies are needed to stimulate cooperation to improve the impact of productions.